2018
DOI: 10.1017/s0022029918000456
|View full text |Cite
|
Sign up to set email alerts
|

Associations of the first occurrence of pathogen-specific clinical mastitis with milk yield and milk composition in dairy cows

Abstract: The aim of this study was to estimate the associations of the first occurrence of pathogen-specific clinical mastitis (CM) with milk yield and milk composition (somatic cell count (SCC), lactose, fat, protein content in milk and milk urea nitrogen (MUN)). We studied 3149 dairy cows in 31 Hokkaido dairy farms in Japan. Five pathogen groups were studied: Streptococcus spp.; Staphylococcus aureus (S. aureus); coagulase-negative staphylococci (CNS); coliforms; and fungi. Test-day milk data and clinical records wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 27 publications
2
12
0
Order By: Relevance
“…It is generally accepted that the SCC increases as soon as udder health deteriorates to boost the immune response for the invasion of pathogens [26]. In our study, lower milk yield, lactose percentage, and urea nitrogen in milk of the MA group were observed, indicating that the cows were indeed having mastitis due to the damage of milk-producing epithelial cells and the increase in the permeability of the blood mammary barrier [27][28][29]. Moreover, the urea nitrogen in milk was lower in the MA group while the ruminal ammonia concentration showed no difference between SC and MA groups, which was in accordance with our previous study [17].…”
Section: Differences Between Cows With High Sccsupporting
confidence: 47%
“…It is generally accepted that the SCC increases as soon as udder health deteriorates to boost the immune response for the invasion of pathogens [26]. In our study, lower milk yield, lactose percentage, and urea nitrogen in milk of the MA group were observed, indicating that the cows were indeed having mastitis due to the damage of milk-producing epithelial cells and the increase in the permeability of the blood mammary barrier [27][28][29]. Moreover, the urea nitrogen in milk was lower in the MA group while the ruminal ammonia concentration showed no difference between SC and MA groups, which was in accordance with our previous study [17].…”
Section: Differences Between Cows With High Sccsupporting
confidence: 47%
“…Bobbo et al [51] found that milk produced by cows infected with mastitis pathogens had a lower lactose content, but statistical differences between contagious, environmental and opportunistic mastitis pathogens were not observed. A lower lactose content was also described in milk with coagulase-negative Staphylococcus [52,53], S. aureus [52,53], coliform bacteria [52,53] and fungal [53] infections. A great decrease in lactose content was also observed in milk samples with yeast infection.…”
Section: Discussionmentioning
confidence: 87%
“…A large number of studies have shown that mastitis can seriously affect the milk yield and milk quality of dairy cows [42], so alleviating mastitis is an important means to improve the milk yield and quality of dairy cows. In addition, some studies have shown that niacin can significantly increase milk yield and milk protein in dairy cows [43].…”
Section: Discussionmentioning
confidence: 99%